Effect of interictal epileptiform discharges on EEG-based functional connectivity networks. Issue 5 (May 2020) - Hu, Derek K.; Mower, Andrew; Shrey, Daniel W.; Lopour, Beth A.
Highlights: Infantile spasms subjects exhibit broadly increased connectivity strength during interictal spikes. Functional connectivity network structure is unaltered by interictal spikes in infantile spasms. Simulated spikes in healthy control EEG did not alter network strength or structure. Abstract: Objective: Functional connectivity networks (FCNs) based on interictal electroencephalography (EEG) can identify pathological brain networks associated with epilepsy. FCNs are altered by interictal epileptiform discharges (IEDs), but it is unknown whether this is due to the morphology of the IED or the underlying pathological activity. Therefore, we characterized the impact of IEDs on the FCN through simulations and EEG analysis. Methods: We introduced simulated IEDs to sleep EEG recordings of eight healthy controls and analyzed the effect of IED amplitude and rate on the FCN. We then generated FCNs based on epochs with and without IEDs and compared them to the analogous FCNs from eight subjects with infantile spasms (IS), based on 1340 visually marked IEDs. Differences in network structure and strength were assessed. Results: IEDs in IS subjects caused increased connectivity strength but no change in network structure. In controls, simulated IEDs with physiological amplitudes and rates did not alter network strength or structure. Conclusions: Increases in connectivity strength in IS subjects are not artifacts caused by the interictal spike waveform and may be related to the underlying pathophysiology of IS. Significance: Dynamic changes in EEG-based FCNs during IEDs may be valuable for identification of pathological networks associated with epilepsy.